2006
DOI: 10.1080/10976640500452083
|View full text |Cite
|
Sign up to set email alerts
|

Co-Registration of Cardiac MRI and Rest Gated SPECT in the Assessment of Myocardial Perfusion, Function and Viability

Abstract: Matching rest perfusion and function in anatomically co-registered myocardial segments in our study confirms that 3-D image co-registration of cine MRI, DE MRI and gated SPECT could be a precise method of integrated visualization of perfusion, function and viability helping in differentiating all forms of reversible and irreversible effects of myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Individual myocardial segments were assigned to coronary artery territories based on available data with little correlation with delineated myocardial segmentation (2). Cardiac magnetic resonance (CMR) imaging has emerged as a powerful noninvasive technique for the evaluation of myocardial function, perfusion, and viability in a single study without the need of radioactive tracers administration, which is a distinct attribute of CMR (3,4). This imaging modality has been shown to have a higher spatial resolution when compared to nuclear perfusion imaging techniques (5).…”
mentioning
confidence: 99%
“…Individual myocardial segments were assigned to coronary artery territories based on available data with little correlation with delineated myocardial segmentation (2). Cardiac magnetic resonance (CMR) imaging has emerged as a powerful noninvasive technique for the evaluation of myocardial function, perfusion, and viability in a single study without the need of radioactive tracers administration, which is a distinct attribute of CMR (3,4). This imaging modality has been shown to have a higher spatial resolution when compared to nuclear perfusion imaging techniques (5).…”
mentioning
confidence: 99%
“…A number of reports have assessed left ventricular (LV) function (Waiter et al 2000, Okuda et al 2005, Sheehan et al 2002, Veress et al 2005, Sandstede 2003, Bax et al 2000, Smedema et al 2004, Misko et al 2006. Waiter et al (2000) compared determinations of reduced wall thickening by MRI to those determined by ECG-gated PET using 18 F-FDG and reported an 81% correlation between the two approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Sheehan et al (2002) assessed myocardial function by integrating contractile function obtained from MRI images and perfusion, and metabolism obtained from PET. Misko et al (2006) reported that 3D image co-registration of cine MRI, delayed enhancement MRI and gated SPECT could be a precise method for integrated visualization of perfusion, function and viability, helping in differentiating all forms of reversible and irreversible effects of myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%